Non-Invasive Ventilation as Primary Ventilator Support for Neonate with Acute Respiratory Failure: A Standardised Regimen of Ventilator Support Decreases Morbidities and Hospital Stay - Manoj Malviya; Neelima K; Kanchan C; Dayal A.; V.S.V. Prasad (JCDR Research and Publications Pvt. Ltd., 2013)
Background: Both conventional ventilation (CMV) and CPAP are frequently used as the primary modality for infant presenting with Acute respiratory failure, however, evidence regarding the "best" primary ventilatory modality is lacking. Aims: To report our experience of nasal CPAP as primary ventilator support strategy in infants admitted for ARF. Design: Retrospective comparative audit over a period of 2 years. Methods: All the infants admitted to NICU requiring respiratory support, in the form of CPAP and/ or CMV, were included in the study. Two cohort chosen for comparison were 1. The CMV era (January-December 2007): CMV as the primary modality. 2. The CPAP era (January-December 2008): CPAP as the primary modality with standardised ventilator regimen. Results: The numbers of infants requiring respiratory support (CMV and/or CPAP) were almost similar (CMV era: 77/308, (25%), CPAP era: 94/372, (25.2%). No statistically significant differences were found in the baseline characteristics. The CPAP era was associated with decreased in incidence of total number of hospital stay (23.5 vs 15.4, p= 0.001), days on mechanical ventilations (8.3 Vs 5.9; p= 0.001), ROP (14.2 Vs 2.1; p= 0.01 ) and NEC (9%, Vs 0%; p= 0.01) but was associated with increased in incidence of pneumothorax (1.2 Vs 9.5; p=0.05). There was no difference in mortality and total number of respiratory support days and culture positive sepsis (16.8% Vs 9.4%; p = 0.23), between the groups. Conclusions: A standardised ventilator regimen with bubble CPAP can be safely use as primary ventilator support for neonate with ARF and associated with decreased hospital stay, NEC and ROP